(untitled) - Martin, John H. (Tokyo, 1993)
Nara: a cultural guide takes the visistor on an indepth investigation of this fascinating repository of Japanese culture. More than a guidebook, it intimately describes the cultural, historical, and artistic forces which made Nara the great political capital it once was and the great cultural capital it remains.